(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Menstruation is a normal physiological process in females starting at the age of twelve years and lasts till the age of fifty years. It is a cyclical phenomenon usually occurring every twenty-one to thirty five days and includes uterine bleeding for about three to seven days. Most well adjusted women experience minor psychological and somatic changes for a few days preceding menstruation. These menstrual molimina give way to a sensation of relief and well being once menstruation is established. Most women of reproductive age have some physical discomfort or dysphoria in the weeks before menstruation. Pre-Menstrual Syndrome is one such commonly reported and highly prevalent disorder characterized by constellation of physical, emotional, cognitive and behavioral symptoms. An 18-year-old female patient reported to OPD with the complaints of pain during menses since six years, extreme mood swings, irritability, sudden tearfulness, anger outbursts, nervousness. These symptoms were also associated with vomiting and loose motions. On physical examination, no abnormalities were detected. Mental Status Examination revealed abnormality in mood and affect, attention, concentration and thought process Based on history, presenting symptoms and diagnostic criteria the case was established as Premenstrual Syndrome. So, the protocol for treatment planned was symptomatic. Internal administration of Gokhura churna plus Yastimadhu with Munnaka kshirapaak was given for 15 days. Rajaswalacharya was advised.